2015
DOI: 10.1097/ede.0000000000000229
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Related to Extreme Temperature for 15 Cities in Northeast Asia

Abstract: Mortality increased with either cold or hot temperature in urban populations of high-income countries in Northeast Asia, with spatial variations of effects among cities and countries. Findings suggest that climate factors are major contributors to the spatial heterogeneity of effects in this region, although further research is merited to identify other factors as determinants of variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 30 publications
6
39
0
Order By: Relevance
“…Comparisons of heat-related illness patterns across multiple cities and countries in northeast Asia (Chung et al 2015) and internationally (Guo et al 2014) reported that despite spatial heterogeneity in frequency, hot temperature was strongly associated with an increase in cardiovascular mortality within a short time lag of 1-3 days. Specific epidemiological reports on regional heat waves, such as in Chicago 1995 (Semenza et al 1996), France 2003 (Fouillet et al 2006), and China (Bai et al 2014), support this direct association between ambient temperature during acute heat waves and increased mortality.…”
Section: Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons of heat-related illness patterns across multiple cities and countries in northeast Asia (Chung et al 2015) and internationally (Guo et al 2014) reported that despite spatial heterogeneity in frequency, hot temperature was strongly associated with an increase in cardiovascular mortality within a short time lag of 1-3 days. Specific epidemiological reports on regional heat waves, such as in Chicago 1995 (Semenza et al 1996), France 2003 (Fouillet et al 2006), and China (Bai et al 2014), support this direct association between ambient temperature during acute heat waves and increased mortality.…”
Section: Heat Stressmentioning
confidence: 99%
“…With climate warming, the impact of heat waves on general population morbidity and mortality risks has been extensively reported in temperate and tropical climates and in both urban and rural regions (Bai et al 2014;Berko et al 2014;Chung et al 2015;Kjellstrom and Weaver 2009;Yip et al 2008). Projections of climate change over the coming century suggest increasing incidences of heat-related mortality in both the general public and in occupational settings (Gubernot et al 2014;Jay and Kenny 2010;Kjellstrom et al 2013;Lundgren et al 2013;Xiang et al 2014).…”
Section: Future Projectionsmentioning
confidence: 99%
“…Research has been done in temperate countries with regard to HW effects, with similar patterns of increased risk in increasing duration and intensity [9,10,13,14,17,18]. Most studies in sub-tropical and tropical cities have observed increased risks at both sides of the temperature extremes, with less or no emphasis on HW [4,1922]. The Philippines, a middle-income country, has not yet fully integrated heat-health action plans, which include the HW risk estimation, regardless of the fact that observed relative risks (RR) are evident in the extreme high temperature [20].…”
Section: Introductionmentioning
confidence: 99%
“…The city-specific level of human heat tolerance among urban populations has been investigated by studies that relate elevated ambient temperature or heat to mortality records of a city (Baccini et al 2008;Ballester et al 2011;Chung et al 2015;Gasparrini et al 2015). However, this information is very local, often provided in incomparable temperature metrics and determined by varying parameters.…”
Section: Heat Burden In Citiesmentioning
confidence: 99%